The Importance Of Investment Decisions Using The Capital Asset Pricing Model (Capm) In Healthcare Provider Company - Sutrisno Adi, Tri (Journal of Comprehensive Science, 2023)
Background:This research tests the Capital Asset Pricing Model (CAPM) in determining the required rates of return on Indonesian healthcare sectors stocks with the actual rates of return. Objectives: To find out the required speed of the Indonesia healthcare reported sector, especially hospital stocks, from December 1, 2021, to November 1, 2022, and compare them with the actual rates of return in the corresponding periods to identify the valuation status of the stocks. Methods:To be an empirical study, we adopted analytical research. The collecting data is from www.yahoo.finance.com and doing analytical research with CAPM Results:The findings show that the Capital Asset Pricing Model (CAPM) did not give any appropriate forecast of the return from healthcare sectors stocks thought the one-year period of study because the result was different from the annual report from this group of hospital companies. ConclusionsThe Capital Asset Pricing Model (CAPM) is not a good predictor of stock return in the Indonesian Stock Exchange healthcare sector.